Combinatory thinking: an approach from the password game (Research, Society and Development, 2020)
The purpose of this article is to present the paths outlined for the development of combinatorial reasoning and the fundamental principle of counting through problem situations arising from the game. The conception of this work arose from the contact with games at the Mathematics Teaching Laboratory (LEM) and from discussions about new teaching methodologies in the Supervised Internship IV discipline of the Full Mathematics Degree course at the State University of Maringá. In this way, in partnership with LEM, this activity proposal was developed, whose target audience was students from the 8th and 9th years of Elementary School. The Password Game was used as a methodological resource, in order to work the multiplicative principle in a playful way and different from the traditional one. The realization of this activity with the students made us realize that it is possible, through the use of games, to trigger very rich mathematical discussions, as well as to promote learning situations in the classroom.